Exercise’s impact on lung cancer molecular mechanisms: a current overview - Mancini, Annamaria; Orlandella, Francesca Maria; Vitucci, Daniela; Luciano, Neila; Alfieri, Andreina; Orrù, Stefania; Salvatore, Giuliana; Buono, Pasqualina (Frontiers in Oncology, 2024)
Lung cancer is the major cause of cancer-related deaths worldwide with an estimated 1.8 million deaths and 2.4 million new cases in 2022. Poor cardiorespiratory fitness, dyspnea and fatigue are the common features in lung cancer patients, partially limiting the exercise prescription. Exercise improves cardiorespiratory and muscular fitness and reduces the risk of some types of cancer, including lung cancer. Recently, the American Society of Clinical Oncology has encouraged preoperative exercise for lung cancer patients. Nonetheless, only limited data, mostly obtained from mouse models of lung cancer, are available on the molecular effects of exercise in lung cancer. Thus, the present minireview aims to shed light on the molecular mechanisms induced by different type of exercise in lung cancer. In particular, the role of the exercise in tumor microenvironment remodeling, angiogenesis, gene expression, apoptosis and intermediate metabolism will be examined.